2021
DOI: 10.3390/ijms22083974
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Molecules Associated with Ultraviolet Radiation-Mediated Skin Aging

Abstract: Skin is the largest and most complex organ in the human body comprised of multiple layers with different types of cells. Different kinds of environmental stressors, for example, ultraviolet radiation (UVR), temperature, air pollutants, smoking, and diet, accelerate skin aging by stimulating inflammatory molecules. Skin aging caused by UVR is characterized by loss of elasticity, fine lines, wrinkles, reduced epidermal and dermal components, increased epidermal permeability, delayed wound healing, and approximat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
118
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(124 citation statements)
references
References 111 publications
4
118
0
2
Order By: Relevance
“…It has been reported that the ability to perform these functions declines with age [ 1 , 2 ]. Skin aging is classified as endogenous aging, also known as chronological aging, and exogenous aging affected by UV, air pollution, alcoholism, and nutritional imbalance [ 3 ]. The major characteristics of aging skin are thinning and reduced turnover of the epidermis, caused by a delayed recovery of skin damage [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the ability to perform these functions declines with age [ 1 , 2 ]. Skin aging is classified as endogenous aging, also known as chronological aging, and exogenous aging affected by UV, air pollution, alcoholism, and nutritional imbalance [ 3 ]. The major characteristics of aging skin are thinning and reduced turnover of the epidermis, caused by a delayed recovery of skin damage [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Skin photoaging caused by UVB exposure over a long period of time causes histological changes, such as irregular changes in keratinocytes, an increase in the number of fibroblasts and inflammatory cells, and an accelerated increase in cross-linked collagen fiber levels in the dermis (Robert et al, 2009). Furthermore, exposure of the skin to UVB also causes ROS production (Ansary et al, 2021;Geng et al, 2021). Exposure to UVB promotes continuous ROS generation in keratinocytes, and ROS are rapidly removed by enzymatic and nonenzymatic methods.…”
Section: Discussionmentioning
confidence: 99%
“…Cytokines are another important element in the skin aging process [65]. Upon UV radiation, several inflammatory signaling pathways are activated via different surface receptors such as epidermal growth factor receptors, the TGF receptor, Toll-like receptors, the interleukin 1 (IL-1) receptor, and the TNF receptor [66]. Major cytokines secreted from keratinocytes are interleukins (IL-1, IL-3, IL-6, IL-8, IL-33), colony-stimulating factors (CSFs) (granulocyte macrophage [GM]-CSF, M-CSF, G-CSF), TGF-α, TGF-ÎČ, TNF-α, and platelet-derived growth factor [67].…”
Section: Cytokines In Aging Skinmentioning
confidence: 99%
“…Telomere shortening In intrinsic aging [48] In chronological aging [49,52] Oxidative stress and matrix metalloproteinases ROS and photoaging [53,55,56] Signal cascade activated by ROS [58,59,61,63,132,133] Cytokines Cytokines released by UV radiation [65][66][67] Tumor necrosis factor α [69] Interleukins [72,73,[77][78][79][80]134] CCN1 [82,83] Autophagic control Association with aging process [92][93][94][95][96][97][98] Apoptosis Association with aging process [104,[107][108][109] MicroRNAs Chronological aging [113][114][115][116][117][118][119]135] photoaging [120][121][122]…”
Section: Molecular Mechanisms Details Referencesmentioning
confidence: 99%